2011
DOI: 10.1029/2010wr009525
|View full text |Cite
|
Sign up to set email alerts
|

Impact of temporal data resolution on parameter inference and model identification in conceptual hydrological modeling: Insights from an experimental catchment

Abstract: [1] This study presents quantitative and qualitative insights into the time scale dependencies of hydrological parameters, predictions and their uncertainties, and examines the impact of the time resolution of the calibration data on the identifiable system complexity. Data from an experimental basin (Weierbach, Luxembourg) is used to analyze four conceptual models of varying complexity, over time scales of 30 min to 3 days, using several combinations of numerical implementations and inference equations. Larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 123 publications
(325 reference statements)
3
72
0
Order By: Relevance
“…This hypothesis is backed by a study comparing catchments of different geology (Onda et al, 2001), where the prolonged response of double-peak hydrographs was identified as an indicator of deeply percolating subsurface flow through bedrock fissures. This theory might also apply to the catchment investigated here, with its fractured schist bedrock (Kavetski et al, 2011). Furthermore, deep subsurface storage overflow (Zillgens et al, 2007) and fast groundwater displacement (Graeff et al, 2009) are processes which may play a role in the behavior of the Colpach River catchment.…”
Section: Synthesis: Functioning Of the Investigated Hillslopementioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is backed by a study comparing catchments of different geology (Onda et al, 2001), where the prolonged response of double-peak hydrographs was identified as an indicator of deeply percolating subsurface flow through bedrock fissures. This theory might also apply to the catchment investigated here, with its fractured schist bedrock (Kavetski et al, 2011). Furthermore, deep subsurface storage overflow (Zillgens et al, 2007) and fast groundwater displacement (Graeff et al, 2009) are processes which may play a role in the behavior of the Colpach River catchment.…”
Section: Synthesis: Functioning Of the Investigated Hillslopementioning
confidence: 99%
“…The schist bedrock below is strongly inclined, with almost vertical foliation, and is considered impermeable but with fractures which can function as a complex flow network with local storage in the rock cracks when saturated (Van den Bos et al, 2006;Kavetski et al, 2011). The subsurface structures are of predominantly geogenic origin and are considered temporally persistent.…”
Section: Study Sitementioning
confidence: 99%
“…Flow-duration curves have previously been used in model calibration by Sugawara (1979), Yu and Yang (2000), as one of the criteria considered by Refsgaard and Knudsen (1996) and by Blazkova and Beven (2009), and as a qualitative measure of model performance, e.g. by Houghton-Carr (1999), Kavetski et al (2011), and Son and Sivapalan (2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of the model time step, or using the equivalent expression in this study, i.e. the time interval of the model input data, on the inference of the catchment structure, model parameters and, more generally, the catchment behaviour remains poorly understood (Kavetski et al, 2011). Furthermore, in operational applications, scientists are more interested in the improvement of the model accuracy and the appropriate use of the observational data rather than reducing the time dependency of the model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It was recommended that in order to obtain the best performance, the model should be calibrated at the same time step as the one used for operation. Following this, a number of studies have been carried out on the time-step dependency of the hydrological model parameters (Finnerty et al, 1997;Tang et al, 2007;Littlewood and Croke, 2008;Wang et al, 2009;Cho et al, 2009;Kavetski et al, 2011), for its implications in regionalisation at ungauged catchments or climate impact analysis, etc. However, the impact of the model time step, or using the equivalent expression in this study, i.e.…”
Section: Introductionmentioning
confidence: 99%